Device for collecting articles - Herdy, Rusnandi; Mohd Azman, Abdullah; Mohd Jailani, Mohd Nor (2015)
A device for collecting at least one article from ground, which comprises: a handlebar having a pair of elongate transverse arms of adjustable length, and a first shaft being transversely connected to the arms ; first means for picking the article; a receptacle for receiving the article; and second means for guiding the article from the first means to the receptacle; wherein the first means has a plurality of wheels grouped into segments by axles, wherein the axle is transversely connected to at least one bracket, and the bracket is pivotally connected to the first shaft, in a way such that the segments are disposed one beside another, and each segment is capable of moving pivotally and independently; and rim of each wheel has a plurality of spaced elongate protrusions.